World HTLV Day – November 10th - Araujo, Adele caterino de (2018)
The November 10th was instituted as the World HTLV Day by the International Retrovirology Association (IRVA), aiming informing and mobilizing the society and the public authorities on the significance of this infection caused by the first known human retrovirus, the human T-cell lymphotropic virus type 1 (HTLV-1). The associated diseases, the impact in the public health, and the means to block its transmission were reviewed. Considering that Brazil, the country in the Latin America, has been presenting the highest number of HTLV-1-infected individuals, this text was written for giving the relevant information concerning the HTLV-1 infection to the scientific community.